Aerobic evaluation of young swimmers using the critical velocity test a brief report - Fernandes, R. (Journal of Physical Education and Sport, 2011)
Critical velocity is the maximal swimming velocity that could be maintained for a long time without exhaustion. As it is considered to be well related with the exercise intensity corresponding to the individual anaerobic threshold, critical velocity has been used to monitor the swimmer`s aerobic performance. However, studies conducted in age-group swimmers are scarce and some literature does not use a long distance test as required for obtaining reliable critical velocity results. The aim of the present study was to assess critical velocity in 11-14 years old swimmers in order to characterize their aerobic capacity. So, 56 girls and 62 boys performed 200 and 800m front crawl tests at maximum intensity, being critical velocity assessed by the slope of the regression line between the test distances and the respective times. Critical velocity values were 1.21±0.06, 1.28±0.05 and 1.25±0.06 m/s for the girls, boys and total group, with significant differences being observed between gender groups. As expected, these results were lower than the values presented in the literature for older swimmers. However, some of these studies that reported significantly higher critical velocity values used short distances tests for its assessment, which could lead to the overestimation of the final results. It is suggested the use of the individual critical velocity converted in 100m time to implement specific training series for aerobic capacity development, as well as for the more precise definition of training volumes and intensities. Thus, the used critical velocity test could be considered a useful training strategy used to increase swimmers conditioning